Water Supply Management Through an Innovative Dashboard Solution - Ms. S. Ashwini; Ms. D. Santhiya (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The increased public awareness and stronger restrictions have led to a rising recognition of the significance of advanced technology, especially Geographic Information Systems (GIS), in the management of water resources. The use of GIS in water management is highlighted in this work, with particular attention paid to pollution control, hydrologic modelling, and analytical water supply systems. Furthermore, by combining six conditioning factors and applying vulnerability analysis and logistic regression, it offers a novel approach to leak detection in water distribution networks (WDNs). In order to support preventive maintenance and resource allocation, the model predicts vulnerable locations properly. It is also suggested to use machine learning algorithms to optimise turbine maintenance schedules as part of a predictive maintenance framework for hydroelectric power facilities. High accuracy rates are attained by the framework, which finds important variables for maintenance prediction. These methods provide useful instruments for effective management of water resources overall.